Penggunaan Media Pembelajaran Berbasis Teknologi dalam Pembelajaran IPAS di Sekolah Dasar - Celsia Ditha Rahmani; Adrias Adrias; Fadilla Suciana (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
The use of technology-based learning media in Natural and Social Sciences (IPAS) learning in elementary schools has great potential to enhance effectiveness and student engagement. However, the implementation of technology in learning still faces various challenges. This study employs a qualitative method with a literature review approach to analyze the challenges and solutions in integrating technology-based learning media in elementary schools. The findings indicate that many schools have not yet optimally utilized technology in IPAS learning. The primary barriers include low digital literacy among teachers, limited infrastructure, lack of policies promoting technology use, and low awareness and interest in technology adoption among teachers and students. This study recommends continuous training for teachers, strengthening educational policies related to technology integration, and improving access to digital infrastructure in elementary schools. With adequate support from various stakeholders, technology integration in IPAS learning can be more effective and widespread, thereby improving the overall quality of education.